Peningkatan Aktivitas Bertanya Dan Hasil Belajar Siswa Melalui Penerapan Pendekatan Keterampilan Proses Pada Materi Pokok Pesawat Sederhana Kelas V Mi Yusuf Abdussatar Kediri Lombok Barat - Yuliana, Elya (Universitas Islam Lamongan, 2017)
The purposes of this research are to increase the students asking activity and student learning outcomes in class V of MI Yusuf Abdussatar Kediri, totaling 23 people. Learning to apply the process skills approach, teaches students to discover and develop the facts by themselves. the concept of learning presenting, students' courage in ideas, opinions and questions, effort, activity and creativity in the learning process and the level of student attitudes that dominate in the learning process. This learning activity helps students to be more active in asking.This research is a classroom action research conducted in two cycles, consisting of the action planning stage, the stage of implementation of the action, observation, and the stage of evaluation and reflection. Students and teacher activity data derived from observations and interviews for the assessment process, while data on student learning outcomes obtained through tests given at the end of each cycle. Indicators of success of this study extend from the average value grade students can reach the KKM 65 and with a percentage of 85%. The results showed that the average value of students in cycle I and II increased from 72.70 into 82.43 with the difference in value of 9.73. While the percentage of students who earn a minimum value standard upward cycle I and II also increased from 73.91% to 86.95% by a margin of 13:04%. This means that action research is in compliance indicators to be achieved. The results showed that the application process can increase the skill of asking activity and science learning outcomes in science teaching class VKey word:Â Process skills, asking question activities, learning outcomes